ANALISIS PENGARUH KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA MALANG SELATAN - Yessica Tanilasari; Pujo Gunarso (University of Merdeka Malang, 2017)
This research aimed to analyze the influence of taxpayers awareness and the quality service tax authorities on individual tax compliance. This research was conducted on Kantor Pelayanan Pajak Pratama Malang Selatan. The population in this research was a non employees individual taxpayers of Kantor Pelayanan Pajak Pratama Malang Selatan. Samples were taken by convenience sampling method, with a total sample of 100 respondents. Methods of data collection carried out using questionnaires. This research using validity and reliability test, and multiple linear regression analysis. The analysis showed that the taxpayer Awareness positive effect on compliance of individual taxpayers. This meant that the higher the level of awareness taxpayer individual taxpayer compliance will also increase. Quality of service fiscus positive effect on compliance of individual taxpayers. This meant that the quality of service that increases the tax authorities, the compliance of individual taxpayers also will increase. Awareness of taxpayers and service quality fiscus positive effect on compliance of individual taxpayers. This meant that an individual taxpayer compliance can be achieved with the existence of two variables: the awareness of taxpayers and the quality of service tax authorities. DOI: https://doi.org/10.26905/ap.v3i1.1324